LEGAL PROTECTION FOR VICTIMS OF DOMESTIC VIOLENCE THROUGH COMPENSATION AND RESTITUTION - Siti Rahmah; Hafrida, Usman (Adisam Publisher, 2025)
Cases of domestic violence can attract the attention of the wider community and cause reactions from various parties, this is because domestic violence is indeed a case that requires special handling from the authorities. Because domestic violence is a type of violence that has unique characteristics, namely that it is carried out in the home, the perpetrators and victims are family members and is often considered not a form of violence. Law No. 23/2004 on the Elimination of Domestic Violence provides a strong legal basis that makes domestic violence, which was originally a household affair, a State affair. Legal protection to victims of crime as part of protection to the community can be realized in various forms such as through the provision of restitution and compensation such as medical services and legal assistance from the state so as not to cause prolonged traumatic effects, that victims of domestic violence, most of whom are women, must receive protection from threats of violence, torture, treatment that is degrading to human dignity. With the existence of Law Number 23/2004 on the Elimination of Domestic Violence, it is hoped that it can be a solution to prevent and overcome domestic violence in law enforcement efforts, in accordance with the principles as intended in Article 3 of Law Number 23/2004 on the Elimination of Domestic Violence, namely: